Creep behavior in Metal Matrix Composite Disc with Thickness Variation - Vandana Gupta (Utilitas Mathematica, 2025)
The objective of the current study is to examine the effect of thermal gradients on stress distributions and the resulting deformation of the revolving functionally graded material disc with hyperbolic thickness in presence of thermal gradients. It has been concluded that the thermal gradients effects the distributions of the stresses and strain rates of the anisotropic rotating disc. Thus, the existence of thermal gradients in revolving disc plays a significant role in behavior of creep.